2014
DOI: 10.1186/1476-4598-13-36
|View full text |Cite
|
Sign up to set email alerts
|

cAMP signaling inhibits radiation-induced ATM phosphorylation leading to the augmentation of apoptosis in human lung cancer cells

Abstract: BackgroundThe ataxia–telangiectasia mutated (ATM) protein kinase plays a central role in coordinating the cellular response to radiation-induced DNA damage. cAMP signaling regulates various cellular responses including metabolism and gene expression. This study aimed to investigate the mechanism through which cAMP signaling regulates ATM activation and cellular responses to ionizing radiation in lung cancer cells.MethodsLung cancer cells were transfected with constitutively active stimulatory G protein (GαsQL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 42 publications
3
36
2
Order By: Relevance
“…Experiments showed that 1) cAMP signaling augmented radiation-induced apoptosis in lung cancer cells, 2) that cAMP signaling reduced SIRT6 expression, 3) that exogenous expression of SIRT6 abolished the cAMP signaling-mediated effects on apoptosis, and 4) that exogenous expression of SIRT6 reduced the level of radiation-induced apoptosis. We previously showed that cAMP signaling regulates apoptosis in various cancer cells, including lung cancer cells, by modulating the expression of Bcl-2 family proteins (8), the expression of X-linked inhibitor of apoptosis protein (22), and the activity of ataxia-telangiectasia mutated (ATM) protein kinase (21). Here, we describe a novel mechanism through which cAMP signaling augments apoptosis, reducing SIRT6 expression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Experiments showed that 1) cAMP signaling augmented radiation-induced apoptosis in lung cancer cells, 2) that cAMP signaling reduced SIRT6 expression, 3) that exogenous expression of SIRT6 abolished the cAMP signaling-mediated effects on apoptosis, and 4) that exogenous expression of SIRT6 reduced the level of radiation-induced apoptosis. We previously showed that cAMP signaling regulates apoptosis in various cancer cells, including lung cancer cells, by modulating the expression of Bcl-2 family proteins (8), the expression of X-linked inhibitor of apoptosis protein (22), and the activity of ataxia-telangiectasia mutated (ATM) protein kinase (21). Here, we describe a novel mechanism through which cAMP signaling augments apoptosis, reducing SIRT6 expression.…”
Section: Discussionmentioning
confidence: 97%
“…Western Blot Analysis-Western blotting was performed as previously described (21). Antibodies against SIRT1, -2, and -7, Skp2, ubiquitin, and p-CREB were purchased from Santa Cruz Biotechnology (Santa Cruz, CA), and antibodies against SIRT6, CHIP, Mdm2, p-c-Raf, c-Raf, p-MEK, MEK, p-ERK, ERK, CREB, p-p38, p38, p-JNK, JNK, poly(ADP-ribose) polymerases (PARP), caspase-3, and FLAG were purchased from Cell Signaling Technology (Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, cAMP signaling inhibits radiation induced phosphorylation of ATM in lung cancer [42]. Addition of forskolin In summary we show that although IR inhibits IL-23 secretion from DC mono-cultures, the inclusion of FB provides a positive feedback loop that serves to maintain IL-23 secretion by DC.…”
Section: Fb Promote Irradiated DC Il-23 Responses Through the Camp Pamentioning
confidence: 99%
“…However PGE 2 also up-regulates IL-23 through activation of the cAMP-PKA (Protein Kinase-A) signaling pathway [40,41]. Interestingly, in lung cancer cAMP signaling inhibits IR-induced phosphorylation of ATM [42]. Therefore, we sought to dissect the molecular mechanism responsible for IL-23 secretion in irradiated DC-FB co-cultures.…”
Section: Fb Promote Irradiated DC Il-23 Responses Through the Camp Pamentioning
confidence: 99%
“…A number of the biological processes identified by GO analysis have been previously reported to be regulated by cAMP. These include mRNA splicing (64)(65)(66), spindle organization (67,68), fibroblast migration (69,70), lamellipodium assembly (71,72), apoptosis (73)(74)(75)(76), ATM signaling (77,78), gene silencing via microRNA (79)(80)(81)(82), T-cell selection (83), and cytoskeletal reorganization (84). This study suggests which molecular substrates might participate in the regulation of these processes.…”
Section: Biological Processes Regulated By Different Pde-regulatedmentioning
confidence: 99%